CONTEMPORARY THERAPEUTIC PRINCIPLES IN THE MANAGEMENT OF PATIENTS WITH POLYCYSTIC OVARY SYNDROME - Simić, Dušan; Živadinović, Aleksandar; Živadinović, Lazar; Beljić, Nikola; Cekić, Miodrag (Acta medicae Medianae, 2024)
Ovarian functional disorder is caused by an imbalance or disorder in the production of sex hormones, leading to irregularity in the menstrual cycles, as well as a reduced ability to conceive or carry to term. There are two types of ovarian dysfunction, i.e. primary, caused by the existence of ovarian pathophysiology, or secondary, which stems from thyroid or pituitary gland dysfunction. Polycystic Ovarian Syndrome, or PCOS, is an endocrine disorder of great complexity, and it was first described in 1935. The syndrome represents the most frequent cause of secondary amenorrhea and ovulatory dysfunction in reproductive-aged women. ‘Syndrome’ signifies a phenotype, or a set of clinical characteristics. Polycystic ovary syndrome involves classic phenotypes with specific characteristics that include the clinical signs of increased serum androgen concentrations, irregular periods, excessive androgen secretion, and infertility, as a consequence. Furthermore, the syndrome should be observed and treated as a metabolic disorder since it is closely associated with hyperinsulinemia and insulin resistance. A complex and individualized therapeutic approach is necessary to combat the complexity of the various disorders observed in various phenotypes. This review has been based on the literature research found in available databases. It presents a review of all the contemporary therapeutic options for managing patients suffering from polycystic ovary syndrome. Still, more studies are required to fully reveal the complex pathophysiology of the polycystic ovary syndrome. For this reason, this subject needs to be tackled in prospective epidemiological studies.